Marc brown's arthur anniversary collection eaudiobook Arthur's mystery envelope, arthur makes the team, arthur accused!, arthur and the lost diary. - Brown, Marc (Arthur., 2008)
Read by Mark Linn-Baker Approx. 2.5 hours 2 CD's This special anniversary package includes four popular stories fromour previous audio collections. Arthur's Mystery Envelope:  A Marc Brown Arthur Chapter Book #1 Arthur's Makes the Team:  A Marc Brown Arthur chapter Book #3 Arthur Accused:  A Marc Brown Arthur Chapter Book #5 Arthur and the Lost Diary:  A Marc Brown Arthur Chapter Book #9